Zavod ali agencija za zaposlovanje - vloga javne institucije na trgu dela - Snoj, Jurij (Delavci in delodajalci, 2012)
The contribution deals with the attitude that should prevail between public and private employment agencies and with other stakeholders in the labour market - competition or cooperation? European Commission proposes that the goal is not to increase competitiveness, but to improve cooperation. Only by involving all stakeholders we can achieve 75% employment rate by 2020. Employment service of Slovenia (ESS) is one of the modern organized European public employment services. By constructive acting as a coordinator of a network of various suppliers in the labour market ESS increase the employability.
Keywords: agencije; javni sektor; javni zavodi; trg dela; zaposlovanje; zasebni sektor